Empowering Young Entrepreneurs: Practical Learning Initiatives in Primary Education - Marlian; Ester Julinda Simarmata; Rosdiana Samosir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
The output of this service shows that the lecture session succeeded in increasing students' understanding of the world of entrepreneurship, while the practice of making small parcels provided direct experience in applying these concepts. The exhibition of student work reveals originality in selecting local materials, helping the local economy, and exploring creative potential in business procedures. Apart from having a good influence on children, strong collaboration between schools, teachers and the surrounding community has also been successful. The complete study shows that the success of this service has helped encourage students' enthusiasm to continue exploring their entrepreneurial potential. The results of this service show that a holistic approach through a combination of lectures and practice of making micro parcels has a good impact on students' understanding of entrepreneurship. However, to ensure sustainability and sustainable growth, follow-up action is needed in the form of building an entrepreneurship program that is integrated into the curriculum and forming small groups to encourage student interest. Thus, this abstract illustrates the effectiveness of this service in arousing curiosity and entrepreneurial creativity at SDN Kuala Geulumpang students, with the aim of being able to make a good contribution to the development of their character and talents in the future.